Take the natural log of both sides: x=(x+2)ln(3)
so x-xln(3)=2ln(3)
or x(1-ln(3))=2ln(3)
so x=2ln(3)/(1-ln(3))
2007-04-18 15:13:26
·
answer #1
·
answered by bruinfan 7
·
1⤊
0⤋
I don't know if this has a solution, since e^x<3^x for any positive value of x, and for negative values, you only go between 0 and 1.
2007-04-18 22:12:19
·
answer #2
·
answered by cattbarf 7
·
0⤊
0⤋
Hey, can I recommend taking the natural log on both sides. So...
e^x=3^x+2
x ln e = x ln3 +2
I can take you that far but I am not sure what comes next. Hope this helps. If you figure out tell.
2007-04-18 22:15:27
·
answer #3
·
answered by aurora 2
·
0⤊
1⤋
e^x = 3^(x + 2)
xln(e) = (x + 2)ln(3)
x = xln(3) + 2ln(3)
x - xln(3) = 2ln(3)
x(1 - ln(3)) = 2ln(3)
x = (2ln(3))/(1 - ln(3))
2007-04-18 22:18:00
·
answer #4
·
answered by Sherman81 6
·
0⤊
0⤋
what are you solving for, e or x?
2007-04-18 22:11:17
·
answer #5
·
answered by mc_bbchs_2010 3
·
0⤊
1⤋
kid, look it up on google
2007-04-18 22:10:21
·
answer #6
·
answered by *Hawaian_Chic_101* 4
·
0⤊
1⤋